An approach to the identification of trypanosoma congolense chromosome-specific hybridization markers. - Apopa, P.L. (University of Nairobi, 1997)
Chromosome rearrangements that occur in trypanosomes appear to affect mainly the medium-sized chromosomes. A possibility exists that non-duplicative activation of telomeric VSG genes might involve chromosome rearrangements occurring several kilobase pairs upstream of the affected VSG gene, thus remaining undetectable by standard gel electrophoresis and southern blot hybridizations with VSG gene probes. Since trypanosomes do not condense their chromosomes at any stage of cell division, this hypothesis cannot be tested by cytological hybridization. Some of the size alterations in chromosomes occur when the trypanosomes are repeatedly passaged, cyclically transmitted through tsetse flies or grown in rodents in the presence of trypanocidal drugs. In some instances, the alterations in the sizes of some chromosomes may relate to a changed phenotype of the parasite. Pulsed field gradient gel electrophoresis (PFGE) of chromosome-sized DNA molecules of lower eukaryotic organisms is an effective way of characterizing such organisms. It has been used to characterize many different isolates of parasitic protozoa including Plasmodium falciparum, Leishmania spp., Trypanosoma spp., Theileria spp. and Toxoplasma. When a particular chromosome rearranges in such organisms, it is impossible to identify the rearranged chromosome in the absence of a marker specific for the chromosome. Short oligonucleotide primers (1O-mers) of arbitrary nucleotide sequences have been used in the polymerase chain reaction (PCR) to generate genomic fingerprints that facilitate the characterization and differentiation of various organisms and for physical mapping of loci which contain genes responsible for identifiable phenotypes. It was proposed that the use of such primers to amplify purified individual chromosomes may generate fingerprints which are characteristic of each chromosome. To test this hypothesis, T congolense clone IL 1180 was used because of its sensitivity to trypanocides and clear pedigree. PFGE conditions were optimized which best separates the four medium-sized chromosomes, whose sizes are: 340 kb, 360 kb, 400 kb and 500 kb. The four chromosomes thus separated were individually purified from agarose gel slices and then peR-amplified with the random primers. The fingerprints of DNA fragments generated were resolved by standard agarose gel electrophoresis. The majority of primers used generated reproducible fingerprints, some of which were polymorphic for the different chromosomes used. In this way, a fragment of DNA was identified which hybridizes only to one of the four chromosomes from which it was amplified by a random primer. Thus, taking this approach, it is feasible to generate chromosome-specific hybridization markers.